Analisis latihan push up untuk meningkatkan kekuatan otot lengan pada peserta ekstrakurikuler bola voli di sekolah dasar - Zaroh, Ayuk Sofika; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2024)
Arm muscle strength is an important part of the body in daily activities. This research was motivated by the unknown nature of push up exercises to increase arm muscle strength in volleyball extracurricular participants in elementary schools. This study aims to find out how strong the arm muscle strength of volleyball extracurricular participants at Masaran 1 Elementary School, both boys and girls, has. This research is a descriptive research. The method used is a survey. The population in this study were volleyball extracurricular participants in elementary schools, totaling 24 boys and 17 girls who were taken using total sampling techniques. The instrument for measuring arm muscle strength is using measurements in the form of a push up physical test. The data analysis technique uses quantitative descriptive analysis presented in percentage form. The research results showed that the push up physical test for male participants was in the